EMS software developement for micro grid - Tian, Tian. (2011)
This project presents a software development of micro grid simulation. In order to create an energy management system for micro grid, a micro grid consisting of wind turbine generator, photovoltaic panel and energy storage system is designed. The software is established by writing programs in language Visual C#. To perform power flow of the power system, Newton-Raphson method is adopted as the power flow algorithm of the micro grid. The power model of wind turbine and photovoltaic panel are based on previous literatures. Using the developed software simulation, the power system network of the designed micro grid is created, and it runs in static and real time mode. From the simulation result, it is found that the micro grid can reliably operate in different situations, which proves the software to be practical.